ISOLATION AND CHARACTERIZATION OF MANNANOLYTIC THERMOPHILIC BACTERIA FROM PALM OIL SHELL AND THEIR MANNANASE ENZYME PRODUCTION PROPERTIES - SUWANTO, ANTONIUS; SUMARDI; HENAWIDJAJA, MAGGY T; URWADARIA, T RESNAWATI P (BIOTROPIA, 2011)
A mannanolytic thermophilic bacterium (L-07) was isolated from palm oil shell after 2 days of enrichment in liquid medium supplemented with 1% palm kernel meal as mannan source. Sequence analysis of 16S-rRNA indicated that L-07 was similar (98%) to Geobacillus stearothermophilus, a species of thermophilic aerobic bacteria. We found that G. stearothermophilus L-07 produced extracellular β-1,4-mannanases, but no β-manosidase and α-galactosidase activities. The growth of L-07 reached its maximum (3.0 x 106 cell/ml) at 12-20 hours, while the highest β-mannanase activity (0.52 U/ml) was observed in culture medium after 36 hours of cultivation at 60o C. The medium containing locust bean gum was the best for producing extracellular β-1,4-mannanases compared with kolang kaling, konjak, and palm kernel meal. SDS-PAGE and zymogram analysis demonstrated that crude mannanase complex of L-07 from locust bean gum containing medium comprised three active bands with molecular weight of 85, 73 and 50 kDa. Keywords : Extracellular enzyme/mannanase/Geobacillus stearothermophilus